Water sanitation in Karachi and its impact on health. (May 2022) - Kumar, Prince; Arshad, Fatima; Shaheen, Sean Kaisser; Nadeem, Arsalan; Islam, Zarmina; Essar, Mohammad Yasir
Abstract: Karachi is the largest city and premiere industrial and financial center of Pakistan yet is subjected to major infrastructure deficits. Of primary concern is poor water sanitation which has predisposed a weak healthcare system and its citizens to increased infectious diseases. In Karachi, causes of this include a mismanaged sewage system, poor urban planning, and overcrowding. Several reasons such as lack of funding, corruption, and mismanagement have exacerbated circumstances placing extra strain on Karachi's already scarce water supply. In addition, lack of maintenance and regulation of the existing system has led to increased contaminated water delivery to citizens. Consequently, outbreaks of various water borne diseases such as typhoid, helicobacter pylori, malaria, diarrhea etc have severely impacted healthcare of citizens, especially with the COVID-19 pandemic. The situation is worsened by Karachi's rapidly growing population and lack of awareness among citizens regarding safe drinking water. Prior socioeconomic disparities, and illiteracy complicate access to medications and appropriate healthcare services. However, despite weak efforts from the government, several national and international organizations continue to strive to improve access to clean, drinkable water.